Connecting accounting and communication: A survey of accounting students throughout univertisties in Malaysia (UiTM, UUM, UPM & UKM) / Halil Paino and Syed Iskandar Syed Idris - Paino, Halil; Syed Idris, Syed Iskandar (2004)
Communication skills are valued highly in public accounting firms, where all professionals at all levels communicate as part of their jobs. However, respondents to a 2000/2002 survey reported that the development of effective communication skills was not part of their formal accounting education and that partners and managers want their entry-level professionals to have these skills onset. Further these skills increase in importance as accounting professionals progress from the entry-level to manager and to partner. Educational institutions need to develop program that include communication topics and courses to prepare accountants for the challenges of their profession.